The metabolism reset diet : repair your liver, stop storing fat, and lose weight naturally - Christianson, Alan (Harmony Books, 2019)
The path to becoming naturally thin isn't as impossible as it may seem. In The Metabolism Reset Diet, you'll unlock the key to rapid, sustained weight loss and lower blood sugar with a four-week cleanse that heals your liver and gives your metabolism new life. The hidden truth is that your liver is actually the key to a healthy metabolism. When it isn't functioning properly, it loses the ability to burn fuel. An overloaded liver can only store fuel as fat - which slows your metabolism and leads to excess weight gain. Even if you cut out sugar and carbs, you can still struggle with weight loss and high blood sugar. With Dr. Alan Christianson's clinically proven program, you'll be able to reverse damage to your liver in just four weeks. Once your liver regains its ability to manage your metabolism, you'll have fewer food cravings, steady energy levels, better digestion, and a metabolism that works optimally. This proven diet is carefully constructed to provide your liver with the nutrients it needs without over fueling, supplying your body with healthy amounts of protein, fiber, micronutrients, and phytonutrients that support liver function. Unlike so many diets that require people to stick to a difficult and restrictive plan, following a liver-friendly eating plan will ensure that your weight and energy stay steady, even if your diet changes. Complete with comprehensive guidelines, meal plans, recipes, and advice on maintenance, The Metabolism Reset Diet will help readers achieve optimal liver function to lose weight and get healthy fast.